The Islamic Legal Perspective on Stocks: A Thematic Hadith Analysis - Aprianti, Sheila; Ilyas, Abustani; Usman, Asiqah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study discusses hadiths related to stock investment from an Islamic perspective, focusing on a hadith narrated by al-Khamsah from ‘Amr bin Syu’aib, sourced from his father and grandfather, which has been authenticated by Tirmidzi, Ibnu Khuzaimah, and Hakim. After confirming the authenticity of the hadith, the next step is to provide syarah (explanation) to clarify its meaning. This research employs the methods of takhrij and syarah, along with a disciplinary approach that includes theological, historical, and philosophical perspectives. The study aims to answer several key questions regarding the content of the hadith on investment, the authenticity of the hadith related to investment, and the explanation of hadiths that support stock investment in Islam. The methodology used is a thematic (maudhui) approach with textual, contextual, and intertextual analysis.In conclusion, Prophet Muhammad (SAW) taught that investment should be conducted with honesty and commitment. The hadith regarding stock investment is accepted and serves as guidance for Muslim practices. Investment is encouraged in Islam, as it can create employment opportunities and prevent the accumulation of wealth. However, it must avoid prohibited elements in both the object and method of investment.